Evaluasi Penampilan Reproduksi Sapi Perah (Studi Kasus Di Perusahaan Peternakan Sapi Perah KUD Sinarjaya) - Siti Darodjah Rasad (Agricultural Faculty, 2009)
Evaluation performance reproduction on dairy cattle (Case study in sinarjaya dairy cattle cooperationABSTRACT. Aim of the identification of performance reproduction was to find out the successfully of reproduction management in the dairy cattle firm or farmers. Performance reproduction of dairy cattle include days open, calving interval, service per conception, first service postpartum and length of the pregnancy. All of that performance reproduction values was ideal value and close relation to the production and that values was difference between farmer and depend of management themselves. Sinar Jaya cooperation is one of dairy cattle cooperation, since 1977 with the population about 1554 dairy cattles in year 2006, has been opportunity to find out the performance reproduction of dairy cattle in that cooperation. Dairy cattle about 197 cattles was used as a sample of the treatment, which were minimum two times calving period with the completely recording of reproduction activity. The method of this research was descriptive method and the data was collected as a census method. As a conclusion, reproduction performance for the first service postpartum, days open and calving interval were ideal values but service per conception was bigger than optimal value.